Prevalence Of Canine Dirofilariasis In And Around Bhubaneswar, Odisha - Rath, P.K.; Panda, S.K.; Mishra, B.P.; Nath, I.; Patra, R.C.; Acharya, A.P.; Mohaptra, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The available literature on the prevalence of dirofilariasis with respect to breed, age and sex is quite meager in India. Dirofilariasis popularly known as ‘Heartworm Disease’ is a common and important disease affecting dogs, cats, foxes and wolves in tropics, sub-tropics and temperate regions of the world. Dirofilaria immitis is the causal agent of heartworm disease in dogs and cats (Genchi et al., 2001). There is apparent increasing prevalence of heartworm disease in canines in India. The aim of the present study was to assess the prevalence of dirofilariasis with respect to breed, age, sex in and around Bhubaneswar, Odisha.